Seasonal predictability of wintertime storminess over the North Atlantic - Qian, BD; Saunders, MA (AMER GEOPHYSICAL UNION, 2003)
[1] Interannual variability in winter storminess over the North Atlantic and Europe causes significant risk and uncertainty. Attempts to seasonally predict winter storminess levels have identified little skill to date. However, recent statistical studies of observational data indicate the presence of marginal but useful skill in predicting the winter North Atlantic Oscillation (NAO). This predictability arises from a significant (p < 0.01) link between northern hemisphere summer snow extent and the coming winter NAO state. We apply this link to assess the seasonal predictability in winter storminess 1972/3-2000/1 at a given point. The correlation skill for predicting, by early September, the numbers of winter gale days and storm force days in the main North Atlantic winter storm track region is between 0.5 and 0.6. Our finding suggests the seasonal predictability of North Atlantic winter storminess may be higher and extend to longer leads than thought previously.